2004
DOI: 10.1046/j.1601-0825.2003.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PI‐HAART on the prevalence of oral lesions in HIV‐1 infected patients. A Greek study

Abstract: Oral lesions were significantly reduced in patients on PI-HAART. A direct anticandidal effect of PI was suggestive and seemed to have accounted, beyond the HAART-related immune reconstitution, for the reduction of candidiasis and all other oral lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 21 publications
8
68
2
1
Order By: Relevance
“…Antiretroviral therapy including inhibitors protease (PIs) can exert a direct effect on Candida virulence by inhibiting the fungal secretory aspartyl proteinases (SAPs) 21 . In this study we did not find significant correlation between the status of Candida carrier and the antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiretroviral therapy including inhibitors protease (PIs) can exert a direct effect on Candida virulence by inhibiting the fungal secretory aspartyl proteinases (SAPs) 21 . In this study we did not find significant correlation between the status of Candida carrier and the antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms seem to play a fundamental role for the declining rates of OPC 9,22 . It has been suggested that low CD4 + lymphocytes count and high plasma HIV RNA levels significantly correlate with oral Candida carriage, thereby increasing the risk of developing symptomatic infections 21 . There are controversies about association of CD4 + cell count and viral load with asymptomatic oral yeast carriage.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that impairment of systemic defense mechanisms by reduction of CD4 ϩ T cells below protective levels and impairment of local immunity by reduction of levels of salivary IgA, defensins, or epithelial cell-mediated cytokines in the saliva might lead to the conversion of commensal Candida to microorganisms with increased pathogenicity, causing an imbalance in the host oral microbial composition and hence increased risk for opportunistic infections (20,21). Dramatic reductions in oral candidiasis after highly active antiretroviral therapy (HAART) have been observed consistently (22)(23)(24)(25); however, the mechanisms underlying host-microbe interactions relative to HIV infection and subsequent HAART, all in the context of oral microbial composition, are not well understood. Currently, a wide range of molecular techniques are available to help identify and characterize microorganisms, including sequencing of 16S rRNA genes using DNA hybridization with custom-designed oligonucleotide probes, fingerprinting of the microbial flora with denaturing gradient gel electrophoresis (DGGE), and other PCR-based techniques.…”
mentioning
confidence: 99%
“…However, an increase in salivary gland disease, xerostomia and oral warts was observed. Taken together, the occurrence rate of Oral mucosal lesions in the post HAART era indicates that Oral mucosal lesions are less frequent, but new and poorly understood paradigms are emerging 34 . The authors emphasize a need for further longitudinal studies with frequent oral examinati ons of children to establish a relati on between HIV and oral health status of HIV positi ve children, parti cularly in relati on to the progression of the disease as esti mated by the depleti on of CD 4 counts in blood.…”
Section: Discussionmentioning
confidence: 99%